2022
DOI: 10.3390/life12122134
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Joint Infection in Mega-Arthroplasty Following Shoulder, Hip and Knee Malignancy—A Prospective Follow-Up Study

Abstract: Introduction: The risk of prosthetic joint infection (PJI) in mega-prosthesis for malignancy is increased compared with non-tumor cases. While several studies describe PJI in tumor-related arthroplasty, prospective studies comparing infection characteristics among different joints are limited. The present study analyzes mega-arthroplasty for hip, knee, and shoulder malignancy and compares the epidemiology, diagnosis, microbe spectrum, treatments, and outcomes between the different entities. Methods: The retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…Age has not been associated with increased risk for PJI in any of the included studies [2,10,12,22]. Although, most of the studies that investigated gender as a potential risk factor for PJI found no correlation [2,17,22], one study reported that male sex was a significant risk factor [12].…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Age has not been associated with increased risk for PJI in any of the included studies [2,10,12,22]. Although, most of the studies that investigated gender as a potential risk factor for PJI found no correlation [2,17,22], one study reported that male sex was a significant risk factor [12].…”
Section: Resultsmentioning
confidence: 83%
“…Additionally, one study conducted a retrospective and prospective analysis focused on a specific time point [2]. Importantly, only one study maintained a prospective followup of their study group [10]. A total of 4.445 patients were included in all studies with a mean age of 35.78 years (range, 4-95 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive bone resections, especially in case of soft tissue involvement for oncological cases, and the following reconstructive phase with the construction and the implant of the prosthetic body require longer surgical times compared to common primary arthroplasty. Furthermore, cases who suffer from malignant bone tumours, especially those who received chemotherapy, often have deficiencies in their immune systems and are therefore more exposed to the risk of post-operative infections 6 , 7 . All these factors, together, explain the high complication rates of infective nature that burden megaprosthetic implants in orthopaedic oncology ( Fig.…”
Section: Introductionmentioning
confidence: 99%